The Farmers' Mutual Cooperation Community's Values in Agriculture - Dasfordate, Aksilas; Winoto, Darmawan Edi; Pangalila, Theodorus (Jurnal Moral Kemasyarakatan, 2024)
The values of farmers' mutual cooperation in agriculture were examined in Javanese society, where challenges related to differences in provider quality hindered the assessment of the indigenous economic landscape. Economic indices from various sectors dating back to 1880 were interpreted. The Quantitative Descriptive method was employed to describe and analyze findings without broad generalizations. Participant statements and their responses were examined to identify discrepancies between research findings and existing theories. Qualitative research methods, including interviews and observational techniques, were used to collect data through oral or written communication, enhancing the compilation of observation reports on contextual learning progress. Data analysis was guided by the Miles and Huberman methodology, which directed the process from data collection to presentation and conclusion. Findings indicated a rapid increase in skilled workers after 1830, particularly among carpenters. The number of carpenters surged due to the arrival of newly trained experts, supporting the transportation of goods from rural areas to major cities and ports. Jepara and Rembang emerged as key centers for ship equipment and furniture production, with Rembang employing approximately 700 carpenters by 1840.